Pengaruh literasi keuangan, gaya hidup, dan inklusi keuangan terhadap perilaku keuangan mahasiswa - Christfigo Barus; Martalena Martalena (Universitas Kristen Maranatha, 2026)
The study of students’ financial behavior is an important area of research, as access to financial services does not necessarily reflect effective financial management. This study examines how financial literacy, lifestyle, and financial inclusion influence the way students behave financially at the Faculty of Digital Business and Law, Maranatha Christian University. A quantitative associative research design was employed, involving 157 respondents from a population of 242 FHBD students of the 2025 cohort. To interpret the result, the study applied multiple liner regression to the Likert-scale questionnaire data. The findings show that lifestyle has a negative and substantial impact on financial behavior, financial inclusion has no significant impact, and financial literacy has a positive and considerable impact. The model explains 40.90% of the variance in financial behavior, with an adjusted r-square value of 0.409 for the three variables. These findings suggest that financial literacy and lifestyle control help students develop healthy financial habits, whereas financial services need to be used appropriately. Overall, the study demonstrates that financial literacy and rational consumption habits can improve the financial behavior of young people.